Apolipoprotein B RNA sequence 3' of the mooring sequence and cellular sources of auxiliary factors determine the location and extent of promiscuous editing. - Sowden, M P (1998)
Apolipoprotein B (apoB) RNA editing involves a cytidine to uridine transition at nucleotide 6666 (C6666) 5' of an essential cis -acting 11 nucleotide motif known as the mooring sequence. APOBEC-1 (apoB editing catalytic sub-unit 1) serves as the site-specific cytidine deaminase in the context of a multiprotein assembly, the editosome. Experimental over-expression of APOBEC-1 resulted in an increased proportion of apoB mRNAs edited at C6666, as well as editing of sites that would otherwise not be recognized (promiscuous editing). In the rat hepatoma McArdle cell line, these sites occurred predominantly 5' of the mooring sequence on either rat or human apoB mRNA expressed from transfected cDNA. In comparison, over-expression of APOBEC-1 in HepG2 (HepG2-APOBEC) human hepatoma cells, induced promiscuous editing primarily 5' of the mooring sequence, but sites 3' of the C6666 were also used more efficiently. The capacity for promiscuous editing was common to rat, rabbit and human sources of APOBEC-1. The data suggested that differences in the distribution of promiscuous editing sites and in the efficiency of their utilization may reflect cell-type-specific differences in auxiliary proteins. Deletion of the mooring sequence abolished editing at the wild type site and markedly reduced, but did not eliminate, promiscuous editing. In contrast, deletion of a pair of tandem UGAU motifs 3' of the mooring sequence in human apoB mRNA selectively reduced promiscuous editing, leaving the efficiency of editing at the wild type site essentially unaffected. ApoB RNA constructs and naturally occurring mRNAs such as NAT-1 (novel APOBEC-1 target-1) that lack this downstream element were not promiscuously edited in McArdle or HepG2 cells. These findings underscore the importance of RNA sequences and the cellular context of auxiliary factors in regulating editing site utilization.